The Structural, Representation, and Interaction Aspects of Governmental Social Networking Account - Lestari Yayuk; Dewi Surya Rahmi; Puspita Yesi (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2014)
This study was inspired by the growth of media and technology, particularly social networking accounts. Such accounts help people interact and participate in political decisions in spite of geographical, time and socio-economic barriers. However, West Sumatera provincial government has yet to optimize media as a means of communicatingwith the public. In the study, we use public sphere theory proposed by Habermas. Dahlgren developed it further into three dimensions: structural, representation, and interaction. Of two accounts examined, i.e. Solok and Pariaman city administrations’, the three dimensionsof public sphere have not existed. Public relations unit as the department that manages the accounts, still puts social networking accounts as a means of image polishing of the institutions rather than a means to disseminate information to the public. Social networking management that has not been taken as a performance appraisal tools has made social networking accounts as an additional task, although essentially they realise the importance to manage them.Keywords: Public sphere, Social networks, structural, representation, interaction